2015
DOI: 10.1515/bmc-2015-0011
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic revival of a dead cardiomyocyte through mitochondrial interventions

Abstract: Mitochondrial dysfunction has been reported to underline heart failure, and our earlier report suggests that mitochondrial fusion and fission contributes significantly to volume overload heart failure. Although ample studies highlight mitochondrial dysfunction to be a major cause, studies are lacking to uncover the role of mitochondrial epigenetics, i.e. epigenetic modifications of mtDNA in cardiomyocyte function. Additionally, mitochondrial proteases like calpain and Lon proteases are underexplored. Cardiomyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…TFAM's regulation of Serca2a decreases cytoplasmic calcium levels, effectively decreasing protease Calpain1 expression. Calcium-driven calpain proteases are responsible for the proteolytic degradation of both contractile and cytosolic proteins (Kunkel et al 2015a). Studies show that calpain upregulation is a major factor in cardiomyocyte functional decline (Takahashi et al 2006).…”
Section: R a F Tmentioning
confidence: 99%
See 1 more Smart Citation
“…TFAM's regulation of Serca2a decreases cytoplasmic calcium levels, effectively decreasing protease Calpain1 expression. Calcium-driven calpain proteases are responsible for the proteolytic degradation of both contractile and cytosolic proteins (Kunkel et al 2015a). Studies show that calpain upregulation is a major factor in cardiomyocyte functional decline (Takahashi et al 2006).…”
Section: R a F Tmentioning
confidence: 99%
“…ROS-driven Matrix-metalloproteinases (MMPs) are zincdependent endopeptidases capable of degrading the exctracellular matrix (ECM) of cardiomyocytes. We have assessed the expression of MMP-9 in cardiac hypertrophy (Givvimani et al 2012) and described MMP upregulation in heart failure as it pertains to ROS generation (Kunkel et al 2015a).…”
Section: R a F Tmentioning
confidence: 99%
“…From a biological and clinical standpoint, the hypomethylation negatively drives the angiogenic and endothelial gene expression, resulting in vascular complications. The mitochondria dynamic also plays a key role in heart failure, as their damage via enhanced ROS runs parallel to free calcium in the cardiomyocytes and volume overload [ 98 ].…”
Section: The Oxidative Circuit In the Cardiovascular System: The Pmentioning
confidence: 99%
“…Moreover, a previous study has exhibited that GA treatment involves in the improvement of metabolic pro le through regulation the gene expression of PGC-1α and SIRT1 in brown adipose tissue of obese mice [52].TFAM as a mitochondrial factor plays a key role in suppressing cardiac remodeling factors, which cause cardiac hypertrophy and heart failure [3]. It has been reported that enhanced TFAM gene expression leads to cellular/functional recovery by decreasing cardiac remodeling [53,54]. Previous investigations indicated that TFAM knockdown results in decreased mitochondrial biogenesis, and dilated cardiomyopathy, indicating TFAM's potential to decrease modulatory factors involve in mitochondrial function and cardiac hypertrophy [55].…”
Section: Discussionmentioning
confidence: 99%